Semi-Сonductor Terahertz Systems of Coherent Reception on the Effect of “Hot-Electrons” - Eru, I. I. (Видавничий дім «Академперіодика», 2012)
Current possibilities and perspectives for employment of the semiconductor hot-electron bolometer mixers in the high-sensitivity terahertz receivers are analyzed.